Biomarkers of Oxidative Stress and Antioxidant Status in Cerebrovascular Disease: Implications for Diagnosis - Jaspreet Kaur; Mridula Mittal; Vishal Gupta; Purnima Jindal; Jaswant Kaur (Medical Science: Trends and Innovations Vol. 2, 2025)
Dysregulation of the balance between oxidative and protective mechanisms is implicated in the pathogenesis of cerebrovascular disease. Elevated plasma angiotensin-converting enzyme (ACE) activity is also recognized as a contributing factor in vascular pathology. Fasting blood samples were analyzed for serum ACE activity, lipid profile (total cholesterol, triglycerides, HDL-C, LDL-C), malondialdehyde (MDA) as a marker of lipid peroxidation, superoxide dismutase (SOD) activity in erythrocytes, and serum vitamin E concentration in stroke and TIA patients and healthy control. The correlation between ACE activity and stroke severity/outcome was also assessed. Serum ACE activity was significantly elevated in both stroke and TIA groups compared to controls. Patients with CVD exhibited significantly increased levels of fasting blood glucose, total cholesterol, triglycerides, LDL-C, and MDA. Conversely, significant reductions were observed in HDL-C, erythrocyte SOD activity, and serum vitamin E concentration in the CVD group compared to controls. These findings suggest that oxidative stress, alongside dyslipidemia, contributes to the pathophysiology of acute ischemic stroke and TIA. The observed oxidant-antioxidant imbalance may be associated with stroke severity. Furthermore, the significant elevation of serum ACE activity in stroke and TIA patients correlates with increased disease severity and poorer outcomes in CVD. This chapter highlights the potential role of ACE and oxidative stress in the development and progression of cerebrovascular events.